Analisis Pengaruh Panjang Baseline Terhadap Ketelitian Pengukuran Situasi Dengan Menggunakan GNSS Metode RTK-NTRIP (Studi Kasus: Semarang, Kab. Kendal dan Boyolali) - Ega Gumilar Hafiz; Moehammad Awaluddin; Bambang Darmo Yuwono (Departement Teknik Geodesi Universitas Diponegoro, 2014)
Developments and requirement about mapping survei in Indonesia are getting faster and the lack of availability of basic point technique used as a point of the belt as well as the least amount of human resources who understand the job of mapping surveis, is one of the factors restricting to produce a map of the situation quickly (real time) and can also provide data quality and a good position. Then it needs a system of measurement that can give results that can satisfy the needs of mapping in Indonesia.Associated with these problems, in this final task has been carried research measurements using GPS CORS (Continuosly Operating Reference Stations) system. By analyzing the influence of the length of the baseline against the accuracy of the measurement situation using GNSS RTK-NTRIP method and using Total Station measurement data as definitive data.The purpose of this measurement is to know the horizontal, vertikal accuracy and scale for plotting the map. The results of analysis and statistical tests will be found horizontal accuration and vertical accuration )it is : the measurement with the long baseline 1 km has a value of = ±0,092 m and = ±0,047 m, with long baseline 15,6 km has a value of = ±0,181 m and = ±0,179 m, and with long baseline 57,6 km has a value of σHZ = ±0,765 m and = ±0,258 m. Refers to the accuration scale map, for long baseline 1 km include of 1: 500 scale map, while the long baseline 15,6 km include of 1: 1.000 scale map, and long baseline 57,6 km include of 1: 1.000 scale map.Keywords: Topographic Mapping, Measurements of GPS, GNSS, RTK (Real Time Kinematic), NTRIP (RTCM Transport Networked via Internet Protocol)